Free to Be Trusted? Organizational Constraints on Trust in Boundary Spanners - Perrone, Vincenzo; Zaheer, Akbar; McEvily, Bill (Organization Science, 2003)
We present a view of trust in boundary spanners as explained by the extent of role autonomy, a multidimensional concept that reflects the discretion that agents have in interpreting and enacting their roles. We argue that, in a buyer-supplier context, purchasing managers will be trusted to a greater extent by supplier representatives when they are free from constraints that limit their ability to interpret their boundary-spanning roles. We conceptualize and measure three key components of role autonomy: Functional influence, tenure, and clan culture. Taken together, these components of role autonomy shape and define the purchasing manager's willingness and capacity to make and uphold commitments to supplier representatives. Role autonomy permits purchasing managers to engage in discretionary behaviors that allow supplier representatives to learn about their underlying motives and intentions. We test hypotheses linking the components of role autonomy to trust on a sample of 119 buyer-supplier relationships. We use a dyadic research design that combines data from purchasing managers and supplier representatives. The results suggest that granting purchasing managers greater autonomy enhances supplier representative trust in purchasing managers. By drawing attention to role autonomy as a feature of organizations that influences trust we highlight the importance of organizational context in contributing to a deeper understanding of trust.